Supporting safe disclosure of sexual violence in healthcare settings: findings from a realist evaluation applying candidacy theory through a trauma-focused lens - Jonathan Ross; Rachel J Caswell; C Bradbury-Jones (BMJ Open)
Objectives Most people who have experienced sexual violence (SV) will disclose the event(s) to someone. Key recipients of disclosure are those working in healthcare, and using sexual and reproductive health services can be an important step in accessing necessary medical care and being signposted to other services. Accessing this care and disclosing SV can be challenging. Evidence is lacking about how best to create a safe environment for disclosure to take place, how services can make changes to better facilitate this experience and what changes matter most.Design Realist evaluation.Setting Sexual and reproductive health settings.Participants 1-1 interviews with service users who have disclosed SV (n=18), three focus groups with healthcare professionals and survey respondents (n=2007).Outcome measures Initial programme theories of what works, for whom and in what context were tested and refined with empirical data from a national survey, 1-1 interviews and focus groups. The final steps are presented here, bringing strands of the study together and informed using substantive theory.Results The key steps in using healthcare on disclosure of SV relate to self-identification as a worthy candidate irrespective of background or presentation, ensuring empowerment during navigation of services, initial access to sexual healthcare made straightforward, validation by healthcare professionals when receiving disclosures, choice and control for service users during a collaborative interaction with healthcare professionals and aftercare that reflects needs particularly of minoritised groups.Conclusions We propose a novel way of considering Dixon-Woods’ candidacy theory seen through a trauma-informed lens for healthcare following SV, and how, by holding a trauma-informed lens to candidacy, steps of healthcare access and utilisation can be framed to ensure a safer environment for disclosure. This modified substantive theory marks the chosen endpoint of the realist evaluation and provides a transferable programme theory that can be considered in other settings.